T Tinjauan Pelaksanaan Sistem Komputerisasi Rekam Medis Di Puskesmas Ngemplak 1 - Andhy Sulistyo (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2023)
The Ngemplak I Health Center already uses the SMARTSEHAT system with a LAN (Local At Network) network, but in its records there are still some things that are done manually. The purpose of this study was to find out the implementation of the medical record computerized system in the reporting section, to identify problems in implementing the medical record computerized system in the reporting section, to find out the efforts made in overcoming obstacles in implementing the medical record computerized system in the reporting section. The method used is descriptive with a qualitative approach. Data collection was carried out by means of observation, interviews, and documentation studies. The subjects of this study were reporting officers and the head of the Ngemplak I Health Center. The object of this study was the implementation of a computerized system in the reporting section. There are obstacles in the reporting section, there are still polys that are not connected to SMARTSEHAT so officers have to provide a form every month to fill it in and also an unstable network hinders the reporting process.